Phenotypical and Functional Characteristics of Human Regulatory T Cells during Ex Vivo Maturation from CD4+ T Lymphocytes - Blinova, Varvara G.; Novachly, Natalia S.; Gippius, Sofya N.; Hilal, Abdullah; Gladilina, Yulia A.; Eliseeva, Daria D.; Zhdanov, Dmitry D. (Applied sciences, 2021)
Regulatory T cells (Tregs) participate in the negative regulation of inflammatory reactions by suppressing effector cells. In a number of autoimmune disorders, the suppressive function and/or the number of Tregs is compromised. The lack of active functioning Tregs can be restored with adoptive transfer of expanded ex vivo autologous Tregs. In our study, we traced the differentiation and maturation of Tregs CD4+CD25+FoxP3+CD127low over 7 days of cultivation from initial CD4+ T cells under ex vivo conditions. The resulting ex vivo expanded cell population (eTregs) demonstrated the immune profile of Tregs with an increased capacity to suppress the proliferation of target effector cells. The expression of the FoxP3 gene was upregulated within the time of expansion and was associated with gradual demethylation in the promotor region of the T cell-specific demethylation region. Real-time RT-PCR analysis revealed changes in the expression profile of genes involved in cell cycle regulation. In addition to FOXP3, the cells displayed elevated mRNA levels of Ikaros zinc finger transcription factors and the main telomerase catalytic subunit hTERT. Alternative splicing of FoxP3, hTERT and IKZF family members was demonstrated to be involved in eTreg maturation. Our data indicate that expanded ex vivo eTregs develop a Treg-specific phenotype and functional suppressive activity. We suggest that eTregs are not just expanded but transformed cells with enhanced capacities of immune suppression. Our findings may influence further development of cell immunosuppressive therapy based on regulatory T cells.